Body mass index and physical fitness in Brazilian adolescents - Lopes, Vitor P. (2019)
Evaluate the relationship between body mass index and physical fitness in a cross-sectional sample of Brazilian youth.Methods: Participants were 3849 adolescents (2027 girls) aged 10-17 years. Weight and heightwere measured; body mass index was calculated. Physical fitness was evaluated with a multi-stage 20 m shuttle run (cardiovascular endurance), standing long jump (power), and push-ups(upper body strength). Participants were grouped by sex into four age groups: 10-11, 12-13,14 years. Sex-specific ANOVA was used to evaluate differences in each physicalQ2fitness item among weight status categories by age group. Relationships between body massindex and each physical fitness item were evaluated with quadratic regression models by agegroup within each sex.Results: The PF of thin and normal youth was, with few exceptions, significantly better thanthe physical fitness of overweight and obese youth in each age group by sex. On the other hand,physical fitness performances did not consistently differ, on average, between thin and normalweight and between overweight and obese youths. Results of the quadratic regressions indicateda curvilinear (parabolic) relationship between body mass index and each physical fitness itemin most age groups. Better performances were attained by adolescents in the mid-range of thebody mass index distribution, while performances of youth at the low and high ends of the bodymass index distribution were lower.